Design analysis, optimization and identification of optimum single-phase linear PM generator using different magnet shape for wave energy conversion - Memon, A.H. (Institute of Electrical and Electronics Engineers Inc., 2017)
This paper presents the analysis, design optimization and identification of optimum linear permanent magnet (PM) generator for marine wave energy conversion using finite element analysis (FEA). The proposed linear generator is analyzed using different shape of magnet such as; trapezoid, triangular, and parallelogram and compared to the conventional linear PM generator. Eventually, it is identified by FEA that magnet shape augments the characteristics and overall performance of linear PM generator. Time-stepping finite element method (FEM) is employed in order to determine the electromagnetic characteristic of proposed design with all magnet shapes. The optimization has been carried out based on leading or principal dimensional ratios and parameters such as; angle of magnets θ, Φ, and β, ratio of Tmr/Tp, Tp/Tmz and ratio of Rm/Re, which have significant effect on the performance of linear PM generator. The induced-EMF, flux-linkage and magnetic flux density produced in winding and in air-gap, respectively are given and linear PM generator identified by FEA with high performance and superior characteristics is presented with its optimal values for aforementioned principal dimensional ratios and parameters. © 2016 IEEE.